2004
DOI: 10.1103/physreve.69.011201
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoresis of dissolved molecules and polymers: Consideration of the temperature-induced macroscopic pressure gradient

Abstract: The movement of molecules and homopolymer chains dissolved in a nonelectrolyte solvent in response to a temperature gradient is considered a consequence of temperature-induced pressure gradients in the solvent layer surrounding the solute molecules. Local pressure gradients are produced by nonuniform London-van der Waals interactions, established by gradients in the concentration (density) of solvent molecules. The density gradient is produced by variations in solvent thermal expansion within the nonuniform te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 20 publications
4
53
0
Order By: Relevance
“…Piazza and Guarino use this model to qualitatively predict the role of electrostatics in the thermal diffusion of charged micelles [8]. In general, these studies use the hydrodynamic equations to calculate a pressure gradient and/or volume force acting locally on the particles that is induced by a non-uniform distribution of solvent molecules or temperature dependent solvent-particle interaction [8,13,14,15,16,17]. Others also include a macroscopic pressure gradient due to the response of the solvent alone to the temperature gradient and this model nearly quantitatively reproduces the mobility of polymers as measured in experiments [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piazza and Guarino use this model to qualitatively predict the role of electrostatics in the thermal diffusion of charged micelles [8]. In general, these studies use the hydrodynamic equations to calculate a pressure gradient and/or volume force acting locally on the particles that is induced by a non-uniform distribution of solvent molecules or temperature dependent solvent-particle interaction [8,13,14,15,16,17]. Others also include a macroscopic pressure gradient due to the response of the solvent alone to the temperature gradient and this model nearly quantitatively reproduces the mobility of polymers as measured in experiments [14].…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies use the hydrodynamic equations to calculate a pressure gradient and/or volume force acting locally on the particles that is induced by a non-uniform distribution of solvent molecules or temperature dependent solvent-particle interaction [8,13,14,15,16,17]. Others also include a macroscopic pressure gradient due to the response of the solvent alone to the temperature gradient and this model nearly quantitatively reproduces the mobility of polymers as measured in experiments [14]. Another approach begins with the kinetic theory of diffusion in a nonuniform temperature field to derive expressions for the Soret coefficient which allow for both positive and negative values of S T [18].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Sect. 1, several workers have developed hydrodynamic/Brownian motion thermodiffusion models, e.g., [9][10][11]. These models, as discussed by Hartung et al [8], are, in general, successful in predicting the experimental data, but usually contain matching parameters that are not easily determined or even well understood.…”
Section: Model Developmentmentioning
confidence: 97%
“…However, later it was shown that Khazanovich model predictions show fair agreement with experimental data [7,8], but the model apparently predicts unphysical correlation between the effective segment size and the chain stiffness [8]. Hartung et al [8] also tested the Semenov-Schimpf hydrodynamic model [9], using a reverse fitting method, and found fair qualitative agreement against the experimental data, with a proper choice of the radius of the polymer monomer. They also tested the Brenner hydrodynamic/ Brownian motion model [10] in a similar way and obtained rather good agreement with the experimental data, provided that the matching parameter of the Brenner model (λ) is chosen to be 3.70.…”
mentioning
confidence: 94%
“…His model can potentially predict a sign change as the two effects have opposing signs. Runyon and Williams (2011) clarified and further developed the thermal flow-field fractionation method (ThFFF) applied to polyacrylates and compared their experimental results with the theories of Semenov and Schimpf (2004) and Mes (2003). They had to estimate the undetermined input parameters in those theories.…”
Section: Thermophoresis In Polymer Mixturesmentioning
confidence: 99%